2016
DOI: 10.1111/dote.12525
|View full text |Cite
|
Sign up to set email alerts
|

Long-term benefit of transoral incisionless fundoplication using the esophyx device for the management of gastroesophageal reflux disease responsive to medical therapy

Abstract: Transoral incisionless fundoplication (TIF) using the EsophyX device has been shown to be effective and safe in patients with Gastroesophageal reflux disease (GERD); however, the subset of patients that would mostly benefit from this technique remains unknown. The aim of this study was to evaluate the long-term efficacy and safety of the TIF procedure in patients with a history of esophagitis or proven chronic GERD who have achieved symptom control with the administration of proton pump inhibitors (PPIs) but d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 32 publications
0
47
1
Order By: Relevance
“…This suggests that patients experienced durable improvement in disease-specific quality of life following TIF, although most patients did require daily PPI therapy to maintain these improvements in the long-term. Studies have shown that TIF is a promising endoscopic procedure with low adverse events, nearly non-existent chronic side effects, and encouraging short- and intermediate-term efficacy [9, 10, 14]. Although we did not directly study chronic side effects in this cohort, side effects of dysphagia, odynophagia, and gas-bloat were rare as assessed by the GERD-HRQL questionnaire.…”
Section: Discussionmentioning
confidence: 90%
“…This suggests that patients experienced durable improvement in disease-specific quality of life following TIF, although most patients did require daily PPI therapy to maintain these improvements in the long-term. Studies have shown that TIF is a promising endoscopic procedure with low adverse events, nearly non-existent chronic side effects, and encouraging short- and intermediate-term efficacy [9, 10, 14]. Although we did not directly study chronic side effects in this cohort, side effects of dysphagia, odynophagia, and gas-bloat were rare as assessed by the GERD-HRQL questionnaire.…”
Section: Discussionmentioning
confidence: 90%
“…Durability of the TIF 2.0 procedure has been demonstrated in multiple studies. 35,7,9,3033 However, most reflux patients do present with a hiatal defect > 2 cm. The transoral incisionless fundoplication has advantages over laparoscopic fundoplication due to the avoidance of the bloat syndrome and its reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…After one year follow-up, patients were reported to be off PPIs in 25% of cases. EsophyX offers advantages over surgery [14][15][16][17], in particular the absence of incision and thus a faster remission, as well as fewer complications in the short and long term compared to the undesirable side effects associated with laparoscopic anti-reflux procedure compromising the results in some patients. Currently published literature suggests that incidence of persistent side effects after TIF is low [4][5][6].…”
Section: Discussionmentioning
confidence: 99%